2022
DOI: 10.3390/tropicalmed7030039
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Neutrophil-to-Lymphocyte Ratio, Lymphocyte-to-Monocyte Ratio, and Platelet-to-Lymphocyte Ratio in the Diagnosis of Erythema Nodosum Leprosum: A Retrospective Study

Abstract: Erythema nodosum leprosum (ENL) is an acute immune complex-mediated condition of the dermis, subcutaneous tissue, and other tissues seen in patients with multibacillary (MB) leprosy, causing severe impairment to patients’ quality of life. To date, there is no standard diagnostic criteria for ENL. We aimed to study the diagnostic value and accuracy of Neutrophil-to-Lymphocyte ratio (NLR), Lymphocyte-to-Monocyte ratio (LMR), and Platelet-to-Lymphocyte ratio (PLR) in diagnosing ENL. This is an analytic retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These genes were CD177, CYSTM1, HP, LRG1, MCEMP1, MMP8, OLFM4, S100A12 , and S100A9 . This was an expected observation based on previous literature reports of neutrophilia during ENL ( 45 – 47 ). Indeed, we also observed higher neutrophil counts in the blood of a subset of ENL patients from the RNAseq cohort with available blood counts by the time they were recruited for the study (LL= 7; ENL = 5) ( Supplementary Figure S1 ).…”
Section: Resultssupporting
confidence: 88%
“…These genes were CD177, CYSTM1, HP, LRG1, MCEMP1, MMP8, OLFM4, S100A12 , and S100A9 . This was an expected observation based on previous literature reports of neutrophilia during ENL ( 45 – 47 ). Indeed, we also observed higher neutrophil counts in the blood of a subset of ENL patients from the RNAseq cohort with available blood counts by the time they were recruited for the study (LL= 7; ENL = 5) ( Supplementary Figure S1 ).…”
Section: Resultssupporting
confidence: 88%
“…NLR values are expected to be used as diagnostic guidance in predicting patients afflicted with OI who may require a more extended stay in the hospital. NLR has been extensively studied as a test that can be a possible diagnostic tool for predicting mortality, host inflammatory responses, and chemotherapy responses [ 32 34 ]. One prospective cohort study identified high NLR as an independent prognostic modality of mortality in critically ill patients during the hospital stay and six months post-treatment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4] In End-Stage Renal Disease (ESRD), NLR is a marker for inflammation and values NLR >6.53 are significantly associated with complication but many other factors can effect on NLR such as hormonal changes, hypovolemic condition, hematological disease or infections and steroid use. [5,6] neutropenia as a component of NLR in hemodialysis is occurred in pulmonary sequestration of neutrophils after complement activation by the dialyzer membrane. Increased expression of neutrophil adhesion receptors, such as CD11b/CD18, suggests that neutrophil adhesion to the capillary endothelium is a possible mechanism.…”
Section: Discussionmentioning
confidence: 99%